Models of community hospitals and state of research in high-income countries: a scoping review - Tan, Min Hui; Seah, Sharna Si Ying; Seah, Xin Yi; Teo, Simone; Leow, Jeremy; Low, Lian Leng (Frontiers in Public Health, 2025)
IntroductionExisting literature have not reviewed the growing spectrum of care models in Community Hospitals (CH) along with the scope of research. We fill this gap by reviewing CHs models in high-income countries.MethodsWe conducted a scoping review according to Arksey & O’Malley’s framework. We searched for articles published between January 2016 to April 2024 in EMBASE, PubMed, and Scopus. Additional studies were identified through snowballing.Results470 studies were included in the review. CHs models in 22 countries were categorized based on healthcare services provided and target patient populations. CHs in 18 countries were found to provide COVID-19 services. CHs in eight countries primarily provide post-acute and rehabilitative services. 40 articles were extracted to synthesize research themes in CHs providing post-acute care. Majority focused on assessing the healthcare needs of patient populations. Other domains include program efficacy, research and educational needs of staff, clinical guidelines reviews, and the community’s role in supporting CHs.ConclusionCHs evolve to meet changing healthcare needs and understanding the state of CHs research would inform potential research directions. Future studies could explore the relationship between post-acute settings and the community, and strategies to enhance staff capability and address barriers to conducting research in post-acute settings.